Culexiregiloricus, a new genus of Nanaloricidae (Loricifera) from the deep sea of the Guinea Basin (Southeast Atlantic) - Gad, Gunnar (Zootaxa, 2009)
A postlarva of Nanaloricidae (Loricifera) was found in the deep sea of the Guinea Basin. This postlarva belongs to a new species, Culexiregiloricus trichiscalida, which also represents a new genus. It inhabits clayish sediments with a high amount of calcitic multi-chambered shells of recent planktonic foraminiferans of 0.25 to 1.5 mm in size. This is the third report of a species of Nanaloricidae from a deep-sea habitat. The postlarva is characterized by a mouth cone divided in a short basal section and being drawn out terminally in to a long and slim mouth tube as second section. It also has distinct filiform and delicate clavoand spinoscalis of the second and third rows all covered with minute trichoids, a lorica divided into eight plates (four broad and four narrow ones, some of which have two to eight transversal undulations) and eight wide intercalary plicae (six broad and two narrow ones, with distinct longitudinal folds), 14 lorica spikes of medium size along anterior rim of lorica. Other characters include eight dorsal papillated flosculi, of which six form clusters of three each on dorsolateral plates, and a caudal end with a broad ventral plate flanked longitudinally by massive elevated cuticular ridges. Together with the three species of the genus Armorloricus and one species of the genus Phoeniciloricus, the new species may form a specific species-group within Nanaloricidae, which is characterized by a long and slim mouth tube as the most obvious character.